Debt Report 2021 Edition II - World Bank Group (World Bank, Washington, DC, 2021)
This is the second of the series of Debt Reports for 2021 to be published online, at regular intervals, over the course of the year. Their aim is to provide users with analyses of evolving trends and development related to external debt and public debt in individual countries and regional groups, with primary emphasis on low- and middle-income countries, and to keep users abreast of debt-related issues and initiatives. Debt Report 2021 Second Edition is focused on the preliminary estimates of external debt stocks at end-2020 for 120 low, and middle-income countries, and information on low- and middle-income countries’ bond issuance in international capital markets in 2020. It also provides an update on the Debt Service Suspension Initiative (DSSI) as well as an overview of a new initiative aimed at creating a comprehensive dataset of domestic debt obligations of low, and middle, income countries.